The metaphoric dance: co-construction of metaphor in cognitive behaviour therapy. (26th October 2015) - Mathieson, Fiona; Jordan, Jennifer; Carter, Janet D.; Stubbe, Maria
Abstract: Attention to client metaphors has been asserted as a way of enhancing cognitive behaviour therapy. Metaphors can be part of the shared language that is co-constructed between clients and therapists. Recent advances in cognitive linguistics have provided the most clearly operationalized method yet to identify metaphors in conversations, allowing analysis of how shared language develops. This study aims to explore how metaphoric shared language develops in early cognitive behaviour therapy sessions. Based on 12 transcripts of early cognitive behaviour therapy sessions, an iterative process led to the identification of a range of therapist and client responses to each other's metaphors, and identification of whether therapists or clients initiated metaphoric exchanges. Types of responses to therapist or client metaphors within three speaking turns were found to be: repetition, rephrasing, exploration, elaboration/extension, or agreement. Bursts of metaphoric exchange were initiated and taken up by therapists and clients at a similar rate. To conclude, therapists need to attend to the occurrence of metaphors and be aware of the range of potential responses that can engage the client in the 'metaphoric dance' (co-construction of shared metaphors). This has the potential to enhance engagement and outcomes though more salient reformulating of the problem for the client.